Analisis Pengaruh Kegagalan Sistem Pendingin Genset Caterpillar 3500 Series - Pamuji Agustiar Ma’sudi1; Wisnu Pracoyo; Firmansyah Azharul; Wilarso Wilarso (Rekayasa Material, Manufaktur dan Energi, 2019)
When the generator set is operating it is often overheated, the load does not match the capacity of the power expended. An early indication of a high cooling system temperature and this affects the reliability of the generator set that is operating. Overheating can be the initial cause of damage to engine components and can cause fatalities. To find out the root cause of damage to overheating in the cooling system must be analyzed. The damage analysis method is to know the generator set operating system and ensure the loading conditions and temperature measurements on the radiator. The main cause of overheating is lack of radiator water, where the lack of water is caused by leakage on the radiator cap, radiator core, dead-end radiator tube, radiator blocking, water leakage from the water pump, leakage from the pipe or radiator hose. To minimize damage to the steps that must be done is, to recondition the radiator in case of damage to the core, radiator tube, and if there is a water leak from the water pump then what must be done is repair or replacement of the water pump. While damage to the pipe or hose must be replaced and if the radiator water is contaminated with oil, flushing of the radiator water must be carried out, doing regular cleaning of the radiator core. From the analysis and some cooling system maintenance actions, to minimize the occurrence of overheating periodic maintenance must be done